Activation and blockade of prelimbic 5-HT6 receptors produce different effects on depressive-like behaviors in unilateral 6-hydroxydopamine-induced Parkinson's rats. (November 2016) - Zhang, Yu-Ming; Zhang, Li; Wang, Yong; Sun, Yi-Na; Guo, Yuan; Du, Cheng-Xue; Zhang, Jin; Yao, Lu; Yu, Shu-Qi; Liu, Jian
Abstract: The role of prelimbic (PrL) 5-HT6 receptors in depression is poorly understood, particularly in Parkinson's disease-related depression. Here we reported that 6-hydroxydopamine lesions in rats decreased sucrose preference and increased immobility time as measured by the sucrose preference and forced swim tests when compared to sham-operated rats, indicating the induction of depressive-like behaviors. Intra-PrL injection of 5-HT6 receptor agonist WAY208466 induced depressive-like responses in sham-operated rats, and produced antidepressant-like effects in the lesioned rats. However, 5-HT6 receptor antagonist SB258585 produced antidepressant-like effects in sham-operated rats, and increased the expression of depressive-like behaviors in the lesioned rats. Neurochemical results showed that intra-PrL injection of WAY208466 and SB258585 decreased or increased dopamine (DA) and noradrenaline (NA) levels in the medial prefrontal cortex, amygdala, habenula and ventral hippocampus in sham-operated and the lesioned rats, respectively. WAY208466 increased the firing rate of PrL glutamate neurons in the two groups of rats, while SB258585 decreased the firing rate of the neurons. Compared to sham-operated rats, the duration of WAY208466 and SB258585 action on the firing rate of glutamate neurons was markedly prolonged in the lesioned rats. The lesion did not change the co-localization of 5-HT6 receptor and glutamate neurons in the PrL. These findings indicate that 5-HT6 receptors in the PrL are involved in the regulation of depressive-like behaviors, which attribute to changes in DA and NA levels in the limbic and limbic-related brain regions. Additionally, the results suggest that the lesion leads to a supersensitization of 5-HT6 receptors on glutamate neurons in the PrL. Highlights: 5-HT6 receptors in the PrL regulated depressive-like behaviors in sham and lesioned rats. Intra-PrL of 5-HT6 agonist and antagonist changed DA, NA levels in the brain regions. 5-HT6 receptors regulated the firing rate of PrL glutamate neurons. The lesion prolonged the duration of the agonist and antagonist action on the neurons. The lesion did not change the co-localization of EAAC1 and 5-HT6 receptor in the PrL.